Minding the children: A longitudinal study of mental state talk, theory of mind, and behavioural adjustment from the age of 3 to 10. Issue 4 (16th August 2018) - Carr, Amanda; Slade, Lance; Yuill, Nicola; Sullivan, Susan; Ruffman, Ted
Abstract: Mothers' use of mental state talk (MST) is linked to young children's performance on false belief tests of theory of mind (ToM) and to their behaviour in social contexts. However, little is known about MST beyond the early years. This investigation is the first to examine continuity in both mother and child MST from preschool (age 3–4 years) to middle childhood (age 10) and examines the role of early maternal MST in children's later ToM and use of MST. We examine the novel association between MST and children's behavioural adjustment from pre‐school into late childhood. Participants were mother–child dyads from a 7‐year longitudinal study. Measures of MST, ToM, and language were administered at home when children were 3 and 4 years old and again at the age of 10. Also at 10, behavioural adjustment was measured using the Strengths and Difficulties Questionnaire. Mother and child MST were highly stable from preschool to later childhood. Early maternal MST accounted for unique variance in later child MST and behavioural adjustment at 10 years of age; children whose mothers used more MST, specifically references to cognitions, when they were 3 or 4 experienced fewer behavioural difficulties (externalising behaviour) when they were 10 years old.